Control Technologies for Emerging Micro and Nanoscale Systems - Eleftheriou, Evangelos; Moheimani, S.O. Reza.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This book comprises a selection of the presentations made at the “Workshop on Dynamics and Control of Micro and Nanoscale Systems” held at IBM Research – Zurich, Switzerland, on the 10th and 11th of December 2009. The aim of the workshop was to bring together some of the leading researchers in the field of dynamics and control of micro- and nanoscale systems. It proved an excellent forum for discussing new ideas and approaches.
From the content: Techniques Developed for High-Speed AFM -- High-Accuracy Atomic Force Microscope -- High-Speed, Ultra-High-Precision Nano - A Signal Transformation Approach -- 2DOF Control Design for Nanopositioning.
Keywords: Control engineering; Nanotechnology; System theory; Control and Systems Theory; Nanotechnology and Microengineering; Systems Theory, Control